Application of bioinspired W/WO3 electrodes electrochemically constructed on microbial biofilm for the disinfection of dialysate contaminated by Candida parapsilosis - Souza, Barbara A. [UNESP]; Giannini, Maria José S.M. [UNESP]; Yonashiro, Monica [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP] (Elsevier, 2023)
The present work investigates the disinfection of dialysate water used in hemodialysis through the application of bioinspired W/WO3 electrodes constructed on microbial biofilm from C. parapsilosis by electrochemical anodization. The bioinspired electrode was photoactivated by UV/Vis or visible irradiation, and the photocurrent was found to be at least twice higher than that obtained for nanoporous W/WO3 electrode in the dialysate water. Under optimized conditions, the photo-electrocatalytic analysis conducted on the bioinspired electrode at Eapp = 1.5 V and under UV/Vis irradiation led to complete fungi inactivation (5 min) and up to 70% of total organic carbon removal monitored during cell lysis after 120 min of treatment. The results show the bioinspired electrode maintains the structural print of the fungi and works as fungus recognition material. The proposed electrode is also found to exhibit higher surface area, which improves adsorption of microorganisms, leading to faster and more efficient degradation compared to nanoporous W/WO3 electrode, with a 30% increase in the degradation of organic matter present in the medium. The findings show that the bioinspired electrode has outstanding advantages when compared with other materials investigated; these advantages include controlled morphology, good reproducibility, higher adsorption on the electrode surface, and higher efficiency in the disinfection of C. parapsilosis, an agent of several cases of contamination in dialysate.
Keywords: Bioinspired W/WO3 electrodes; Candida Parapsilosis inactivation; Disinfection of dialysate; Photoelectrocatalysis for disinfection